(untitled) (Journal of Dhaka Medical College, 2023)
ANCA vasculitis, caused by antibodies named ANCA (anti-neutrophilic cytoplasmic autoantibodies), is an autoimmune disorder affecting small blood vessels of the body. Among p-ANCA and c- ANCA, c-ANCA (cytoplasmic ANCA) usually targets proteinase three inside neutrophils, causing inflammation of blood vessels. Herein, we report a case of a 56-year-old female patient with c- ANCA-associated vasculitis. The patient presented with a localized skin thickening on the medial aspect of the left thigh and an oral ulcer. Skin biopsy shows erythema induratum (nodular vasculitis). After several investigations, we found c-ANCA positive and concluded the diagnosis as c-ANCA-associated vasculitis. We treat the patient with injectable methylprednisolone, injectable cyclophosphamide, and Mesna. Then we gave oral mycophenolate mofetil and prednisolone. J Dhaka Med Coll. 2022; 31(1) : 158-162